Cybersecurity Policy Framework in Saudi Arabia: Literature Review - Alhalafi, Nawaf; Veeraraghavan, Prakash (Frontiers in Computer Science, 2021)
Saudi Arabia has a goal of ensuring that it has at least two cities among the top 100 smart cities of the future. However, increasing connectivity and incorporation of smart solutions in cities still raises concerns over cyber security with threats arising daily including denial of services and phishing as some of the most significant. Saudi Arabia, therefore, needs a cybersecurity policy framework that will ensure effective protection for all stakeholders in the smart city from these cyber threats. User acceptance is foremost important in any new technology, including smart-cities. Due to ongoing cyber threats and in the absence of an efficient cyber policies, Saudi end-user community is not keen to accept newer technologies where their interaction with online medium is required. The proliferation of smart cities globally affords the opportunity to analyze and compare the efforts made in Saudi Arabia with other nations like the USA, India and Singapore which is the premier smart city model in the globe currently. This review looks at the similarities and differences between KSA’s cyber security policy framework with these three nations. The review will note some of the defining characteristics and approaches to cyber security in the smart cities of USA, India, and Singapore. After reviewing the current framework in Saudi Arabia, this paper will make suggestions such as updating Saudi’s cybercrime legislation like in the US or formulating a master cyber security plan as seen in Singapore that will improve KSA’s framework creating the best framework model for cyber security in its smart cities.